Chest Expansion and Modified Schober Measurement Values in a Healthy, Adult Population - Özge İLLEEZ MEMETOĞLU and Bülent BÜTÜN and İlhan SEZER (Archives of Rheumatology, 2016)
Objectives: This study aims to demonstrate chest expansion and lumbar mobility using modified Schober measurement values in healthy male and female populations aged 15 and over, and to identify factors affecting these measurements. Patients and methods: The prospective study included 444 volunteers (195 males, 249 females; mean age 47.13 years; range 15 to 88 years) from among patients presenting to the Akdeniz University Faculty of Medicine Hospital Physical Medicine and Rehabilitation Clinic. Participants were divided into seven 10-year age groups: group 1: 15-24 years, group 2: 25-34, group 3: 35-44, group 4: 45-54, group 5: 55-64, group 6: 65-74, and group 7: over 75. Exclusion criteria comprised factors potentially influencing spinal mobility and chest expansion. All volunteers’ chest measurements were performed in three planes (circumferential with a tape measure, and anteroposteriorly and transversely with calipers) and lumbar mobility was measured using the modified Schober method. The same physician performed the measurements. Results: Chest expansion measurements using tape and calipers varied considerably in all age groups and in both sexes. While there was no difference between males and females in circumferential chest expansion measurement, there was a significant difference decrease in both sexes from group 3 and onward. The only difference between the sexes in terms of modified Schober measurement was in group 4, in favor of male sex. Age-related change in both sexes was higher at age 55 and above compared to the young age groups. Conclusion: We may conclude that chest expansion measurement in the circumferential plane is sufficient when appropriate conditions are established and provides the most accurate result by permitting measurement in all planes.